Defining the Type of M&E System : Clients, Intended Uses, and Actual Utilization - Briceño, Bertha (World Bank, Washington, DC, 2012)
This is the second note in a monthly series on government monitoring and evaluation (M&E) systems led by the PREM Poverty Reduction and Equity Group under the guidance of Jaime Saavedra, Gladys Lopez-Acevedo, and Keith Mackay, with contributions from several World Bank colleagues. The main purpose of this series is to synthesize existing knowledge about M&E systems and to document new knowledge on M&E systems that may not yet be well understood. The series targets World Bank, donor staff who is working to support client governments in strengthening their M&E systems, as well as government officials interested in learning about the uses and benefits of M&E and in adopting a more systematic approach toward M&E in their governments.